Implementasi Pembangunan Jalan Desa dalam Meningkatkan Konektivitas Wilayah di Kabupaten Rote Ndao - Yurlanda N Foenale (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study analyzes the implementation of village road development in improving regional connectivity in Rote Ndao Regency. Field conditions indicate that although the length of village roads has increased, the proportion of roads in good condition has declined, with most of the road network remaining in damaged and severely damaged conditions. This situation reflects ongoing challenges in maintaining the quality and sustainability of village road infrastructure. This study employs a qualitative approach using a literature review method by collecting secondary data from scientific journals, government performance reports, development planning documents, and relevant media articles. The literature review process is conducted through thematic grouping and content analysis to identify patterns, constraints, and policy implications related to village road development in Rote Ndao Regency.The findings reveal that: (1) the implementation of village road development has not been optimal; (2) supporting factors include government commitment and the availability of regulations, while inhibiting factors include limited inter-agency coordination and the quality of human resources; (3) the community responds positively to village road development; and (4) the road development that has been implemented has proven to improve regional connectivity, with tangible impacts on economic productivity and access to education, health services, and other public services.The conclusion emphasizes that village road development plays a strategic role in supporting regional connectivity and community welfare. Therefore, improvements in infrastructure quality and institutional capacity are necessary to achieve sustainable and optimal development outcomes